Determination of National Specificity of Perceiving the Concept “Learning” in German and Russian through the Association Experiment - Elena Antonovna TULUSINA; Aida Gumerovna SADYKOVA; Charles Frederic CARLSON (Astra Salvensis, 2019)
The article attempts to determine the national specificity of the concept “learning” in German and Russian by means of free association experiment. In the experiment, intermediate school students from different types of institutions of learning in Germany and Russia took part. The resulting associate words made it possible to reveal the general and nationally specific in the conceptual sphere of the students, and also to determine the attitude towards German and Russian teaching of schoolchildren. The scientific novelty is as follows: the concept “learning” is first analyzed from the standpoint of revealing the national specificity of the linguistic means of its verbalization in the German and Russian linguistic worldimage. The relevance of this article is determined by the high importance of the concept “learning” for German and Russian cultures of language, as well as the need to study vocabulary from the perspective of presentation of cultural values. It was found with the help of experimental method that in the sphere of concepts the German school students realize the lexical and semantic variant of the lexeme Lernen – human activity, which consists in mastering knowledge and mastering skills and abilities. The acquisition of a profession or specialty as a variant of the lexical and semantic meaning of the lexeme Lernen is imagined by the pupils of German schools to a far lesser degree, and the perception of this concept in the meaning of “being a student of an educational institution” is presented quite insignificant and implicit in the conceptual sphere of German students.